2013
DOI: 10.1152/ajpregu.00103.2012
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of cyclooxygenase-2 in the mouse increases arterial blood pressure with no impairment in renal NO production in response to chronic high salt intake

Abstract: Staehr M, Hansen PB, Madsen K, Vanhoutte PM, Nüsing RM, Jensen BL. Deletion of cyclooxygenase-2 in the mouse increases arterial blood pressure with no impairment in renal NO production in response to chronic high salt intake. Am J Physiol Regul Integr Comp Physiol 304: R899 -R907, 2013. First published March 27, 2013 doi:10.1152/ajpregu.00103.2012.-Experiments were designed to test the hypothesis that cyclooxygenase-2 (COX-2) activity attenuates the blood pressure increase during high NaCl intake by stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…A previous study has observed that female FVB/N mice also develop a greater increase in BP in response to a HS diet compared to male counterparts 26 , indicating that the BP elevation in Balb/C mice may not be an anomaly, but rather, a representation of a genetic predisposition for salt sensitivity in these strains of female mice that parallels the human population. Notably, data in the C57BL/6 mouse indicates that no such salt-sensitive hypertension persists in females of that genetic background 11 . Therefore, strain and genetic specificity is particularly important for salt-sensitivity studies in females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has observed that female FVB/N mice also develop a greater increase in BP in response to a HS diet compared to male counterparts 26 , indicating that the BP elevation in Balb/C mice may not be an anomaly, but rather, a representation of a genetic predisposition for salt sensitivity in these strains of female mice that parallels the human population. Notably, data in the C57BL/6 mouse indicates that no such salt-sensitive hypertension persists in females of that genetic background 11 . Therefore, strain and genetic specificity is particularly important for salt-sensitivity studies in females.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this discrepancy in the human population, the majority of studies of salt-sensitivity in animal models have been restricted to male animals. Background strains such as the C57BL6 mouse and Sprague-Dawley rat have not been reported to develop salt-sensitive hypertension spontaneously in males or females 10, 11 . Therefore, transgenic models have traditionally been utilized to examine mechanisms of salt-sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Staehr’s results also confirmed the increased BP in COX-2 knockout mice with no impairment in renal NO production in response to chronic high salt intake. (55, 56, 58) COX-2 inhibitors or the genetic absence of COX-2 markedly augments the constrictor actions of angiotensin II (59). …”
Section: Discussionmentioning
confidence: 99%
“…31 The impact of COX-2 in renal sodium handling has been demonstrated using COX-2-deficient mice, which developed marked hypertension in response to high salt diet. 62 A previous study showed that diuretic effects of furosemide and hydrochlorothiazide are partially mediated by COX-2 activation. 20 Therefore, intact COX-2 function is critical to the renal sodium handling and its normalization by candesartan observed in the present study may have significantly contributed the improvement of the sodium balance in our rat model.…”
Section: Discussionmentioning
confidence: 99%